Age-Related Differences in Contribution of Rule-Based Thinking toward Moral Evaluations - Caravita, Simona C. S.; De Silva, Lindamulage N.; Pagani, Vera; Colombo, Barbara; Antonietti, Alessandro (Frontiers in Psychology, 2017)
This study aims to investigate the interplay between different criteria of moral evaluation, related to the type of the rule and context characteristics, in moral reasoning of children, early and late adolescents. Students attending to fourth, seventh, and tenth grade were asked to evaluate the acceptability of rule breaking actions using ad-hoc scenarios. Results suggest that the role of different moral evaluation criteria changes by age. During adolescence a greater integration of the moral criteria emerged. Moreover, adolescents also prioritized the evaluation of moral rule (forbidding to harm others) violations as non-acceptable when the perpetrator harms an innocent victim by applying a direct personal force. The relevance of these findings to increase the understanding of how moral reasoning changes by age for the assessment of impairments in moral reasoning of non-normative groups is also discussed.